2010
DOI: 10.1007/s11102-010-0217-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of prolactinomas in Brazil: an electronic survey

Abstract: Dopamine agonists are the treatment of choice for prolactinomas. However, there are still controversies concerning dose, treatment duration and criteria for drug withdrawal in different clinical situations. The aim of this study was to assess diagnostic and therapeutic approaches to prolactinomas among members of the Brazilian Society of Endocrinology and Metabolism (SBEM). SBEM members answered a questionnaire sent by e-mail that included 18 questions related to controversial issues about the management of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…A similar study conducted in Brazil has been previously published [32]. In the case of pregnancy, only 58 % and 70 % of respondents advocated discontinuation of treatment with dopamine agonists in patients with macroprolactinomas and microprolactinomas, respectively.…”
Section: What Are the Current Trends In The Management Of Prolactinommentioning
confidence: 56%
See 1 more Smart Citation
“…A similar study conducted in Brazil has been previously published [32]. In the case of pregnancy, only 58 % and 70 % of respondents advocated discontinuation of treatment with dopamine agonists in patients with macroprolactinomas and microprolactinomas, respectively.…”
Section: What Are the Current Trends In The Management Of Prolactinommentioning
confidence: 56%
“…In the case of pregnancy, only 58 % and 70 % of respondents advocated discontinuation of treatment with dopamine agonists in patients with macroprolactinomas and microprolactinomas, respectively. Finally, only 36 % would allow breast-feeding without restriction, 44 % would restrict it to patients with microprolactinomas, and 20 % would not recommend it for women with prolactinomas [32].…”
Section: What Are the Current Trends In The Management Of Prolactinommentioning
confidence: 99%
“… The data of Brazil and MENA are derived from Ref. ( 4 , 5 ) respectively. P values using the Chi-square test (or Fisher’s exact test).…”
Section: Resultsmentioning
confidence: 99%
“…However, in the current clinical practice, there are still controversies concerning appropriate diagnosis and treatment of prolactinoma, such as the identification of hyperprolactinemia, the choice of treatment methods, the duration of drug treatment and management of pregnancy and breastfeeding. In recent years, two studies have conducted questionnaire surveys of clinicians’ management of prolactinomas reflecting self-reported clinical diagnoses and treatment ( 4 , 5 ). However, no similar data are available from China.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal duration of therapy with DA for patients with prolactinomas or non-tumoral hyperprolactinemia remains controversial ( 12 ). There is however strong and growing evidence that discontinuation of dopamine agonist treatment may be successfully achieved in a selected group of patients treated for at least 2 years ( 14 17 , 19 , 20 ). A recent systematic review and meta-analysis has shown that the pooled proportion of patients with persisting normoprolactinemia after CAB withdrawal was 35% in a random effects model ( 21 ).…”
Section: Discussionmentioning
confidence: 99%